Effects of chocolate supplementation on metabolic and cardiovascular parameters in ApoE3L mice fed a high‐cholesterol atherogenic diet. Issue 11 (15th August 2013) - Yakala, Gopala K.; Wielinga, Peter Y.; Suarez, Manuel; Bunschoten, Annelies; van, Jolanda M.; Arola, Lluis; Keijer, Jaap; Kleemann, Robert; Kooistra, Teake; Heeringa, Peter
<x xml:space="preserve">Abstract</x> Scope Dietary intake of cocoa and/or chocolate has been suggested to exhibit protective cardiovascular effects although this is still controversial. The aim of this study was to investigate the effects of chocolate supplementation on metabolic and cardiovascular parameters. Methods and results Four groups of ApoE*3Leiden mice were exposed to the following diet regimens. Group 1: cholesterol‐free control diet (CO). Group 2: high‐dose (1.0% w/w) control cholesterol (CC). Group 3: CC supplemented chocolate A (CCA) and Group 4: CC supplemented chocolate B (CCB). Both chocolates differed in polyphenol and fiber content, CCA had a relatively high‐polyphenol and low‐fiber content compared to CCB. Mice fed a high‐cholesterol diet showed increased plasma‐cholesterol and developed atherosclerosis. Both chocolate treatments, particularly CCA, further increased plasma‐cholesterol and increased atherosclerotic plaque formation. Moreover, compared to mice fed a high‐cholesterol diet, both chocolate‐treated groups displayed increased liver injury. Mice on high‐cholesterol diet had elevated plasma levels of sVCAM‐1, sE‐selectin and SAA, which was further increased in the CCB group. Similar effects were observed for renal inflammation markers. Conclusion The two chocolate preparations showed unfavorable, but different effects on cardiometabolic health in E3L mice, which dissimilarities may be related to differences in chocolate composition. We conclude that discrepancies reported on the effects of chocolate on cardiometabolic health may at least partly be due to differences in chocolate composition.